Illocutionary Speech Acts On Instagram Comments of Abigail Muria’s Interview: Cyber Activism Analysis - Simanjuntak, Jessica Ruth Margaretha; Turnip, Novi Kanaya Perdana; Dalimunte, Sukma Rahayu; Azman, Dinda Aqiila; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This research analyzes illocutionary speech acts in Instagram comments on Abigail Muria’s interview with Al Jazeera English, focusing on the context of Indonesian protests in 2025. Using Searle’s theory of speech acts, the study classifies netizen comments into five types: assertive, directive, commissive, expressive, and declarative. The researchers analyzed 29 comments found based on some requirements: most-liked comments, in the form of sentences, minimum 1 row maximum 6 rows, and related to the context. Through qualitative descriptive and quantitative method, also cyber discourse analysis, the findings show that expressive acts, such as thanking, encouraging, criticizing, and praising, are the most dominant, followed by assertive acts expressing agreement or criticism.  These comments reflect strong emotional and cognitive engagement with Indonesia’s political situation. Additionally, directive and commissive acts show how users use social media to mobilize action and express solidarity. This study highlights how online interactions serve as a form of cyber activism, allowing users to participate in political discourse, challenge authority, and amplify their voices globally. Ultimately, the research underscores the importance of digital platforms as spaces for collective expression and social change in the digital age.